Cα-trace model of the transmembrane domain of human copper transporter 1, motion and functional implications - Schushan, Maya (National Academy of Sciences, 2010)
The trimeric human copper transporter 1 (hCTR1) is essential for copper uptake and is implicated in sensitivity to chemotherapy drugs. Using the cryoelectron microscopy (cryoEM) map of hCTR1 and evolutionary data, we constructed a Cα-trace model of the membrane region. The model structure, supported by mutagenesis data, was used to investigate global dynamics through elastic network models. Identified as dominant hinge regions, hCTR1’s MxxxM and GxxxG motifs were shown to have significant roles in functional movements characterized by the two slowest modes of motion. Both modes predicted significant changes at the wide cytoplasmic pore region; the slowest mode introduced a rotational motion around the pore central axis, whereas in the following mode the cytoplasmic parts of the helices approached and moved away from the pore center. In the most cooperative mode, the MxxxM motif in the extracellular narrow region remained static. The second mode of motion, however, predicted a cooperative rotational motion of this copper-binding motif, possibly reflecting activation at the pore’s extracellular entrance. We suggest a molecular mechanism of copper transport in which this motif serves both as a gate and as a selectivity filter. We also suggest residues that are responsible for pH activation.